The Effect of Good Corporate Governance on the Sustainability of Electric Company in Indonesia - RIO AFRIANDA ST MT (International Humanities and Applied Science Journal, 2022)
This study aims to analyze the effect of Good Corporate Governance on the Sustainability of Electricity Companies in Indonesia. The research is based on the GCG Assessment Score from the company's annual report for the last three years. It was found that the aspect of commitment to the implementation of sustainable governance was increasing every year; the aspect of shareholder assessment and GMS decreases; Board of commissioners/board of supervisors increased; The assessment aspect of the Board of Directors decreases every year, and the value of other aspects increases every year. From the total GCG Assessment score of 89.559 in 2020, it is concluded that the implementation of GCG is in the very good category and has a positive effect on the company's sustainability.Keywords: Good Corporate Governance